Impact of Plant Growth-Promoting Rhizobacteria Inoculation and Grafting on Tolerance of Tomato to Combined Water and Nutrient Stress Assessed via Metabolomics Analysis - Kalozoumis, Panagiotis; Savvas, Dimitrios; Aliferis, Konstantinos; Ntatsi, Georgia; Marakis, George; Simou, Evridiki; Tampakaki, Anastasia; Karapanos, Ioannis (Frontiers in Plant Science, 2021)
In the current study, inoculation with plant growth promoting rhizobacteria (PGPR) and grafting were tested as possible cultural practices that may enhance resilience of tomato to stress induced by combined water and nutrient shortage. The roots of tomato grown on perlite were either inoculated or not with PGPRs, applying four different treatments. These were PGPR-T1: a mix of two Enterobacter sp. strains (C1.2 and C1.5); PGPR-T2: Paenibacillus sp., strain DN1.2; PGPR-T3: Enterobacter mori, strain C3.1; and PGPR-T4: Lelliottia sp., strain D2.4. PGPR-treated plants were either self-grafted or grafted onto Solanum lycopersicum cv. M82 and received either full or 50% of their standard water, nitrogen and phosphorus needs. The vegetative biomass of plants subjected to PGPR-T1 was not reduced when plants were cultivated under combined stress, while it was reduced by stress to the rest PGPR treatments. However, PGPR-T3 increased considerably plant biomass of non-stressed tomato plants compared to all other treatments. PGPR application had no impact on fruit biomass, while grafting onto ‘M82’ increased fruit production compared to self-grafting. Metabolomics analysis in tomato leaves revealed that combined stress affects several metabolites, most of them already described as stress-related, including trehalose, myo-inositol, and monopalmitin. PGPR inoculatiοn with Enterobacter mori, strain C3.1 affected metabolites, which are important for plant/microbe symbiosis (myo-inositol, monopalmitin). The rootstock M82 did not affect many metabolites in plant leaves but it clearly decreased the levels of malate and D-fructose and imposed an accumulation of oleic acid. In conclusion, PGPR are capable of increasing tomato tolerance to combined stress. However, further research is required to evaluate more strains and refine protocols for their application. Metabolites that were discovered as biomarkers could be used to accelerate the screening process for traits such as stress tolerance to abiotic and/or abiotic stresses. Finally, ‘M82’ is a suitable rootstock for tomato as it is capable of increasing fruit biomass production.